Deictic Expressions Used by Lera Boroditsky in TED Talks Channel - Ningsih, Putri Dinia; Megawati, Fika (REiLA : Journal of Research and Innovation in Language, 2022)
Highlighting the importance of deictic expression studies in English language context, particularly in the form of speech, it is pivotal to explore further deixis as the specific area of pragmatics in order to enrich the theory as well as the practice of verbal communication development. Thus, the purpose of this descriptive qualitative study is to determine the presence of deixis in Lera Boroditsky’s speech of “how language changes the way we think?” and to decipher the meaning of each deictic statement in her speech. The data were obtained from a video of the TED Talks channel on YouTube. Then the transcript of the speech was analyzed and evaluated by using Levinson’s (1983) and Huang’s theories (2014). The results demonstrated that Lera Boroditsky’s speech has six categories of deixis: person deixis, spatial or place deixis, temporal or time deixis, social deixis, discourse deixis, and emotional deixis. Each deictic phrase has a distinct meaning depending on the context or situation presented in the speech. In other words, recognizing deixis in a formal speech helps understand the intention of speakers with different personalities, backgrounds, and cultures in several types of communication. In addition, some implications of the findings on the process of teaching and learning English language is also elaborated in this study.